Strategies targeting the IL-4/IL-13 axes in disease. Issue 1 (September 2015) - May, Richard D.; Fung, Michael
Abstract IL-4 and IL-13 are pleiotropic Th2 cytokines produced by a wide variety of different cell types and responsible for a broad range of biology and functions. Physiologically, Th2 cytokines are known to mediate host defense against parasites but they can also trigger disease if their activities are dysregulated. In this review we discuss the rationale for targeting the IL-4/IL-13 axes in asthma, atopic dermatitis, allergic rhinitis, COPD, cancer, inflammatory bowel disease, autoimmune disease and fibrotic disease as well as evaluating the associated clinical data derived from blocking IL-4, IL-13 or IL-4 and IL-13 together.